Cover. (25th March 2019) - Hierweger, Alexandra Maximiliane; Engler, Jan Broder; Friese, Manuel A.; Reichardt, Holger M.; Lydon, John; DeMayo, Francesco; Mittrücker, Hans‐Willi; Arck, Petra Clara
Abstract : The cover image is based on the Original Article Progesterone modulates the T‐cell response via glucocorticoid receptor‐dependent pathways, by Alexandra Maximiliane Hierweger et al., DOI10.1111/aji.13084 .